1983
DOI: 10.1246/bcsj.56.592
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Structures and Spectra of a Novel Diquinone; 1,4 : 5,8-Anthracenediquinone

Abstract: Assignment of the electronic absorption spectrum of 1,4 : 5,8-anthracenediquinone (1,4 : 5,8-ADQ) has been carried out with the aid of magnetic circular dichroism and LCAO MO SCF CI calculations including all valence electrons. The lowest energy absorption region of 1,4 : 5,8-ADQ has been revealed to be composed of the n-π* transition or transitions. The higher energy absorption region has been concluded to consist of four π-π* transitions, which are regarded as Lb, La, Ba, and Bb in the Platt’s notation for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 21 publications
4
13
0
Order By: Relevance
“…The former polarisation corresponds to benzenoid, the latter to quinonoid x -7c * transitions (if a polarisation perpendicular to the molecular plane is not considered), in agreement with that reported in ref. 11 and with previous assignments. '-* (11).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The former polarisation corresponds to benzenoid, the latter to quinonoid x -7c * transitions (if a polarisation perpendicular to the molecular plane is not considered), in agreement with that reported in ref. 11 and with previous assignments. '-* (11).…”
mentioning
confidence: 70%
“…11 and with previous assignments. '-* (11). The absorption spectrum of (11) shows a new structured band at ca.…”
mentioning
confidence: 70%
“…77 These results have earlier provided a reference for theoretical investigations at different levels of theory. 18,23,32,[76][77][78] A TD-DFT study, 18 in particular, showed contradictory results with respect to the experimental data, which makes NQ and AQ interesting test cases for our MCD-ADC scheme. Given the size of NQ and AQ, only RICC2 and ADC(2) are considered.…”
Section: B Purine and Hypoxanthinementioning
confidence: 99%
“…[23] The absorption and electrochemical properties of this tetrone, which is the most stable anthracenetetrone according to a computational study, [24] were reported decades ago. [11,25] In a more recent study, the binding of this tetrone on graphene was computationally predicted to be the strongest of several electroactive compounds for green battery electrodes. [26] Such strong binding benefits the cycling performance of batteries.…”
Section: Introductionmentioning
confidence: 99%